Basic Education Through the Lens of Internationalization: The Case of Bohol Province - Cajilog, Aly Marie L.; Pabalan, Asuncion P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The internationalization of basic education in the Philippines is crucial for fostering global competencies, enhancing intercultural understanding, and promoting the country's competitiveness in the rapidly globalizing world. This study aimed to investigate the readiness, challenges encountered, and lived experiences of teachers and school administrators towards internationalization in basic education in the selected public schools in Bohol and Tagbilaran City divisions for the school year 2022–2023. It employed a mixed-method research design, specifically explanatory-sequential or Quantitative-qualitative research. In the quantitative phase, the researcher used a survey method. In the qualitative phase, she conducted an interview. Quantitative data were analyzed using descriptive statistics, while qualitative data was analyzed using thematic analysis. Joint Display analysis was used to determine how the qualitative findings corroborated the quantitative results. The sample comprises 300 respondents from the Tagbilaran City and Bohol province Divisions. Findings revealed that schools were largely prepared in curriculum and student services aspects but lacked in areas such as teacher qualifications and facility upgrades. Participants emphasized the value of cultural awareness, flexible learning, and proficient teaching skills for globalization. Despite this, the study uncovered major obstacles like inadequate e-library and ICT services, institutional challenges, community issues, and less motivation of faculty members towards advanced education. These results offer insights for decision-makers, school heads, and educators to improve school readiness for internationalization. Recommendations were proposed to enhance the readiness and address the concerns, issues, and gaps in the internationalization of basic education.